ANALISIS YURIDIS TERHADAP PUTUSAN HAKIM DALAM TINDAK PIDANA PEMALSUAN SURAT (STUDI KASUS PUTUSAN PN PANGKALAN BUN NOMOR: 255/PID.B/2020/PN PBU) - Umam, Khoirul; Hartoyo, Hartoyo; D, Sri Sukmana (Gapenas Publisher, 2025)
This study aims to analyze the application of substantive criminal law and the judge’s considerations in deciding cases of forgery of COVID-19 rapid-test certificates as reflected in the Decision of the Pangkalan Bun District Court Number 255/Pid.B/2020/PN Pbu. This research employs a normative juridical method using statutory and case approaches. The findings indicate that the judges have considered the elements of forgery as stipulated in Article 263 of the Indonesian Criminal Code and imposed punishment based on principles of justice and legal certainty. The analysis also highlights the challenges of law enforcement during the COVID-19 pandemic, particularly the emergence of new crime patterns such as health document forgery